Unmasking Hidden Threats Global Spread of MBL Resistance Exposed: Membuka Kedok Ancaman Tersembunyi Penyebaran Global Resistensi MBL yang Terekspos - Ali Hussain Anaid Taaban; Muntadhar Shakir Neama Ali; Sura Haidar Mutashar Azgair Azgair; Fatima Muzahim Qasim (Academia Open, 2024)
This study aims to establish a routine monitoring system for MBL enzymes to provide timely data to healthcare professionals and policy makers, enabling informed decision making on antibiotic use and resistance management. Using a combination of molecular biology techniques and data analysis, we monitor MBL activity in various institutional settings. The increasing prevalence of multidrug-resistant (MDR) bacteria is a significant threat to public health globally. Metallo-beta-lactamase (MBL), an enzyme that confers resistance to a wide range of beta-lactam antibiotics, is particularly concerning due to its ability to spread rapidly in healthcare and community settings. Despite the importance of this issue, systematic monitoring and understanding of MBL remains inadequate. Our findings reveal a significant, previously unreported presence of MBLs, underscoring the urgent need for targeted antibiotic stewardship programs. The implications of this study emphasize the importance of integrating enzyme monitoring into standard healthcare practices to reduce the spread of MDR bacteria. Highlights: Regular Monitoring: Essential for tracking MBL enzyme prevalence and guiding antibiotic use. Advanced Techniques: Molecular biology methods enhance MBL detection and analysis. Policy Integration: Crucial for implementing enzyme monitoring in healthcare to combat MDR bacteria spread. Keywords: MBL Enzymes, Antibiotic Resistance, Healthcare Monitoring, Molecular Biology, Stewardship Programs